2003
DOI: 10.1891/0047-2220.34.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Rehabilitation Success Among African American and Caucasian SSDI Recipients with Mild Mental Retardation

Abstract: The purpose of this study was to identify disparities in rehabilitation success (closure status 26) rates between Caucasian and African American SSDI recipients with mild mental retardation. A split-half cross-validation research design was utilized to evaluate two samples (i.e., screening and calibration) of case records obtained from the RSA-911 database for fiscal year 1998. Logistic regression analysis revealed that the odds of rehabilitation success for a Caucasian VR customer was almost two times the odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Deaf and hard of hearing consumers who received college and university training as a VR service were more likely to become competitively employed when also receiving job search assistance, job placement assistance, maintenance, rehabilitation technology, and other services. Job placement services have a long history of being related to positive outcomes for VR consumers, such as African American and Caucasian social security disability insurance recipients with mental retardation (Moore, Alston, Donnell, & Hollis, 2003), recipients of social security disability insurance and supplemental security income (Rogers, Bishop, & Crystal, 2005), deaf non-Latinos (Moore, 2002a), consumers with mental retardation (Moore et al, 2000;Moore, Feist-Price, & Alston, 2002;Moore, Harley, & Gamble, 2004), deaf and hard of hearing consumers (Moore, 2001c), and prevocational deaf consumers (Moore, 2002c). Whereas job search assistance prepares consumers in their search for job leads and opportunities, job placement involves referrals to jobs that result in interviews (Rehabilitation Services Administration, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Deaf and hard of hearing consumers who received college and university training as a VR service were more likely to become competitively employed when also receiving job search assistance, job placement assistance, maintenance, rehabilitation technology, and other services. Job placement services have a long history of being related to positive outcomes for VR consumers, such as African American and Caucasian social security disability insurance recipients with mental retardation (Moore, Alston, Donnell, & Hollis, 2003), recipients of social security disability insurance and supplemental security income (Rogers, Bishop, & Crystal, 2005), deaf non-Latinos (Moore, 2002a), consumers with mental retardation (Moore et al, 2000;Moore, Feist-Price, & Alston, 2002;Moore, Harley, & Gamble, 2004), deaf and hard of hearing consumers (Moore, 2001c), and prevocational deaf consumers (Moore, 2002c). Whereas job search assistance prepares consumers in their search for job leads and opportunities, job placement involves referrals to jobs that result in interviews (Rehabilitation Services Administration, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Whitney, Timmons, Gilmore, and Thomas (1999) looked specifically at the effects of the Rehabilitation Act amendments, comparing data from 1988, 1993, and 1995 to examine changes on key data elements. Moore, Alston, Donnell, and Hollis (2003) used RSA-911 data to study rehabilitation outcomes in White and African American DI recipients and found that the odds of success for a White VR customer were almost twice those for an African American customer. Paugh (2003) identified five VR services as significant predictors of enhanced income at VR case closure.…”
Section: Rsa Closure Recordsmentioning
confidence: 99%
“…These rates compare with an overall successful closure rate of 46.3% for individuals with severe/profound MR in Moore et al (2002b), a 63.9% for individuals with mild/moderate MR in Moore (2001), and a 39% success rate for individuals with MR, cerebral palsy, and epilepsy in Gilmore et al (2000). In addition, Moore et al (2003), when using two samples, reported overall success rates of 71.9% and 73.6% for White customers with mild MR in comparison with 60.4% and 57.2% for African American customers with mild MR. However, the rates from Gilmore et al (2000) are for competitive employment closures only.…”
Section: Research Questionmentioning
confidence: 87%
“…Although mental retardation and autism are both developmental disabilities, each has its own characteristics, and inclusion of research on employment outcomes for customers with mental retardation is not meant to confuse or stereotype characteristics of either disability (Graziano, 2002;Muller et al, 2003). Moore, Alston, Donnell, and Hollis (2003) found that customer race was statistically significantly related to successful closure for customers with mild mental retardation, with White customers having a higher rate of successful closure. Moore (2001) examined relationships among customer characteristics, services provided, and employment outcomes for people with mental retardation.…”
mentioning
confidence: 99%